Improving Environmental Care Attitudes of Early Childhood By Utilizing Recycled Materials - Suharni Suharni; Sri Wahyuni; Yuli Astri (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2021)
Attitude of caring for the environment can be improved since early age and influenced by the impact from environment. This research is purposely to Increase the attitude of caring for the environment Through recycle. This research was classroom action research, with subjects aged 5 to 6 years old in class B who totaling 10 children, 5 boys and 5 girls. The dependent variable from this research is attitude of caring for the environment intelligence whereas the independent variable is the use of used goods. The data collection was gathered by observation to some child on early childhood education institutions. The technique of data analysis was done through descriptive. The result showed that the attitude of caring for the childs environment intelligence could improve after getting an action. The action given was through recycling. The result showed that in pre cycle, the average percentage reached 39,53% with low criteria. And the result of the study, it can be ignored that the proportion of increasing environmental awareness among children aged 5-6 years, the average number after data analysis of pre-cycle activities is in the Low category. Then in cycle one the average number is in the Medium category, and in cycle II the figure has reached the High category